Pengaruh Produksi dan Impor Kendaraan Roda 4 Terhadap Pengangguran Di Provinsi Jawa Barat - Muhammad Ibrahim Baihaqi; Arga Christian Sitohang (Widya Balina, 2025)
Abstract. This study aims to analyze the effect of four-wheeled vehicle production and imports on the unemployment rate in West Java Province during the 2016–2023 period. The background of the study stems from the fluctuating conditions of vehicle production and imports, as well as West Java's unemployment rate, which tends to be higher than the national average. The study employed a quantitative approach with secondary data obtained from Statistics Indonesia (BPS) and the Indonesian Association of Indonesian Automotive Manufacturers (GAIKINDO). The analytical method used was multiple linear regression to determine the simultaneous and partial effects between variables. The results show that four-wheeled vehicle production and imports simultaneously have a significant effect on the unemployment rate. Partially, four-wheeled vehicle production has a significant negative effect, meaning that increased production can reduce the unemployment rate in West Java. Conversely, four-wheeled vehicle imports have no significant effect on the unemployment rate, so increased imports do not directly affect labor absorption. The coefficient of determination of 83.4% indicates that production and imports contribute significantly to explaining variations in the unemployment rate. These research findings emphasize the importance of strengthening the automotive industry sector as a strategy to reduce unemployment in West Java.